Enzyme Control Over Ferric Iron Magnetostructural Properties. (2nd December 2021) - Wang, Huan; Cleary, Michael B.; Lewis, Luke C.; Bacon, Jeffrey W.; Caravan, Peter; Shafaat, Hannah S.; Gale, Eric M.
Abstract: Fe 3+ complexes in aqueous solution can exist as discrete mononuclear species or multinuclear magnetically coupled species. Stimuli‐driven change to Fe 3+ speciation represents a powerful mechanistic basis for magnetic resonance sensor technology, but ligand design strategies to exert precision control of aqueous Fe 3+ magnetostructural properties are entirely underexplored. In pursuit of this objective, we rationally designed a ligand to strongly favor a dinuclear μ‐oxo‐bridged and antiferromagnetically coupled complex, but which undergoes carboxylesterase mediated transformation to a mononuclear high‐spin Fe 3+ chelate resulting in substantial T1 ‐relaxivity increase. The data communicated demonstrate proof of concept for a novel and effective strategy to exert biochemical control over aqueous Fe 3+ magnetic, structural, and relaxometric properties. Abstract : We introduce a first‐in‐class stimuli responsive Fe 3+ complex that is switched between discrete antiferromagnetically coupled and high‐spin paramagnetic species through the action of a carboxylesterase enzyme. We also demonstrate how enzyme‐mediated switching of Fe 3+ magnetic properties offers a mechanistic foundation for new bioresponsive magnetic resonance sensor technology.